Material flow analysis of the nitrogen loading to surface water of Miyun reservoir watershed under uncertainty. (15th June 2022) - Cai, Yanpeng; Xu, Wen; Ji, Daobin; Yang, Zhifeng; Fu, Qiang
Abstract: Nitrogen (N) was one of the primary causes to water environment depravation, having a thorough understanding of N loading to water body is important for reducing the N pollution purposefully. In this research, we took the Miyun reservoir watershed as a typical area, of which a material flow model of the N metabolism was built. Afterwards, the material flow analysis (MFA) was conducted to identify the main pathways that generated N loading. And then the Monte Carlo (MC) method was applied to make uncertainty analysis of the N loading calculated through the MFA. The MFA results showed that the total N loading to surface water of the Miyun reservoir watershed was 5505.42 × 10 3  kg N, of which about 74.89% was originated from the agriculture subsystem (i.e., crop planting, fruit planting and vegetable planting subsystems). The main pathways of the agriculture subsystem that generated N loading were recognized as maize, chestnut, apple, pear, cabbage, cucumber and tomato planting. The uncertainty analysis results revealed that the N loading calculated from the MFA had some uncertainty, of which the fruit planting and industry subsystem had the biggest uncertainty, while the N loading from the fish farming subsystem had the lowest uncertainty. To make directed actions to protect the water quality of the Miyun reservoir watershed, the main pathways of each subsystem that generated N loading need to be regulated. This study provided a new framework of combing the MFA and MC method to simulate N loading to surface water at watershed scale, and was of vital significance to provide decision support for the watershed N pollution management globally.